Gasification Of Rice Husk For Energy Generation For Domestic Needs - Sani Muhammad; Samuel, M.,; Solomon, W.C.; Sa’ad, A.; Haruna, A.; Kingsley, O. (Academy Journal of Science and Engineering)
The study was on the gasification of rice husk specie (O.glaberima popularly known as Jamila), for the purpose of generating energy. A downdraft gasifier, with an initial design conditions of 5 kW thermal power output was considered. The design analysis of the gasifier provided the following specifications: reactor hopper volume and height, throat diameter and height, fuel consumption rate, and outlet diameter of gas pipeline, of 0.00334 m3 and 92 mm, 0.054 mm and 0.08 mm, 1.64 kg/hr, and 19mm. While the design of the blower revealed the following specifications which includes: 8.9 kg/hr air flow rate, 314.2 rad/sec angular speed of blower, 653 N/m torque and 205.2 W power. While the characteristics of the rice husks include 49.21% C, 44.70% H, 3.82% S, 0.79% N2 and 1.41% O2 with HHV LHV of 4.1 MJ/Nm2 and 3.73 MJ/Nm2, respectively. While the proximate analysis shows the following contents as 4.38% moisture, 15.44% ash, 60.83% volatile matter and 23.73% fixed carbon. The results obtained from the gasification shows that 4.8 m3/hr of syngas was generated which composed of 10.4% CH4, 11.02% CO, 3% H2, 1.5% CO2 15% O2 and 0.0102% S. The efficiency of the gasifier was evaluated at 72%.